Development of process for the production of arjuna herbal ghee from buffalo milk - PARMAR, PANKAJ; KHAMRUI, KAUSHIK (The Indian Journal of Animal Sciences, 2017)
The present study was envisaged to develop a process of production of herbal ghee from buffalo milk using arjuna extract. Three different types of extracts viz. commercial aqueous arjuna extract powder, aqueous extract and alcoholic extract prepared in laboratory from arjuna bark were tried. It was observed that, amongst the three types of extracts when added at the level of 4% of the fat taken, ghee prepared using alcoholic extract was found superior. While selecting the level of alcoholic extract for maximizing the retention of phytosterol in ghee, it was found that there was no significant difference in overall acceptability scores of ghee samples prepared by adding the extract @ 5%, 6% and 7% by the weight of fat taken. Phytosterol content was found to be the highest, i.e. 0.38 and 0.47 mg/g when cream and butter were used as fat source at 7% level of addition of alcoholic extract, respectively. Based on the above results, the optimized product was the one that was prepared by addition of 7% alcoholic arjuna extract using creamery butter method. The chemical composition of the optimized product was found to be fat 99.92%, moisture 0.08%, free fatty acid 0.22% oleic acid, Butyro Refractometer reading 41.5 at 40°C, Reichert-Meissl value 31.5 and phytosterol content 0.39 mg/g.